Finite Difference Simulation on Biomagnetic Fluid Flow and Heat Transfer with Gold Nanoparticles towards a Shrinking Sheet in the Presence of a Magnetic Dipole - Ghulam Murtaza; Lata Bonik; Efstratios Em. Tzirtzilakis; Mohammad Ferdows (Computer Sciences & Mathematics Forum, 2023)
In this paper, we study the laminar, incompressible, and steady flow of a biomagnetic fluid, such as blood, containing gold nanoparticles through a shrinking sheet in the presence of a magnetic dipole. This model is consistent with both the principles of magnetohydrodynamics (MHD) and ferro-hydrodynamics (FHD). An effective numerical method that is based on an iterative process, tridiagonal matrix manipulation, and a common finite difference method with central differencing is used to generate the numerical solution of obtained ordinary differential equations (ODEs). The major numerical results show that the fluid velocity decreases as the ferromagnetic number increases whereas the skin friction coefficient shows the opposite behavior. As the ferromagnetic number increases, the rate of heat transfer with ferromagnetic interaction parameter is likewise observed and shown to be decreasing.